Pengaruh Disiplin Kerja, Keselamatan Kerja dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan PO. Sumber Alam Kutoarjo - Angelina Ika Paksi Pramudyta; Hardin Hardin; Fitri Rahmawati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the influence of work discipline, occupational safety, and occupational health on employee productivity at PO. Sumber Alam Kutoarjo. The background indicates that these factors are important in improving employee welfare and maintaining the company’s continuity. This study uses a quantitative method. Data were collected by distributing questionnaires to all employees at PO. Sumber Alam Kutoarjo, totaling 125 people. Analysis was conducted using multiple linear regression with the assistance of SPSS software. The results of the study show that all three variables together have a significant effect on employee work productivity. Individually, the variables of occupational safety and occupational health have the greatest influence compared to the other variables. The research conclusion states that occupational health and safety are the most influential and positive factors in improving employee productivity. Meanwhile, the findings regarding the negative impact of work discipline require further research.